Does Portfolio-Based Language Assessment Align with Learning-Oriented Assessment? Evidence from Literacy Learners and their Instructors - Abbott, Marilyn L.; Lee, Kent K.; Ricioppo, Sabine (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
A high-stakes Portfolio-Based Language Assessment (PBLA) protocol that was fully implemented in all Language Instruction for Newcomers to Canada (LINC) programs in 2019 requires instructors and students to set language-learning goals and complete, compile, and reflect on numerous authentic language tasks. Due to the language barriers incurred when communicating with beginner English-as-a-second-language literacy learners (BELLs), no PBLA research has been conducted with BELLs. To address this gap, we interviewed 26 BELLs (n = 2 from 13 L1s) and their instructors (n = 4) about their understanding and use of PBLA. Student interviews were conducted with the assistance of bilingual interpreters in the students’ L1s. All the interviews were then transcribed and thematically analyzed in relation to PBLA’s alignment with the six dimensions in Turner and Purpura’s (2016) learning-oriented assessment framework: contextual, elicitation, proficiency, learning, instructional, interactional, and affective. Results have implications for optimizing learning, and task-based instruction and assessment practices in LINC.